2007
DOI: 10.1007/s00259-007-0551-x
|View full text |Cite
|
Sign up to set email alerts
|

Activity-based costing evaluation of [18F]-fludeoxyglucose production

Abstract: INTRODUCTION: As healthcare expenses are escalating in many countries, the sector faces a new challenge of becoming more cost efficient. There is an urgent need for more accurate data on the costs of healthcare procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…Most of the known probes (such as 18 F-FDG (9,10) and 3′-deoxy-3′- 18 F-fluorothymidine (11)) involve 2 synthetic steps that are precluded by radioisotope concentration and followed by purification and formulation of the injectable dose. Others (e.g., 2′-deoxy-2′- 18 F-fluoro-5-methyl-1-β-D-arabinofuranosyluracil (12) or 18 F-fluoroazomycin-arabinoside (13)) require longer synthetic procedures that may limit their clinical use.…”
mentioning
confidence: 99%
“…Most of the known probes (such as 18 F-FDG (9,10) and 3′-deoxy-3′- 18 F-fluorothymidine (11)) involve 2 synthetic steps that are precluded by radioisotope concentration and followed by purification and formulation of the injectable dose. Others (e.g., 2′-deoxy-2′- 18 F-fluoro-5-methyl-1-β-D-arabinofuranosyluracil (12) or 18 F-fluoroazomycin-arabinoside (13)) require longer synthetic procedures that may limit their clinical use.…”
mentioning
confidence: 99%
“…They concluded that in traditional method the cost of non-profit deposits is less than civil participation and credit sales while civil participation and credit sales have been equal in cost and also using activity-based costing helps to calculate the exact costs of each one of the activities (studying, approving, paying, supervising and liquidating activities) which help the improvement of organizational activities' efficiency. Krug et al (2008) presented a paper entitled: "Activitybased costing evaluation of [18F]-Fludeoxy Glucose production", and assessed the production of (F-FDG), using Positron Emission Tomography (PET) by using activity-based costing system. The cost of performing positron emission tomography service is extremely affected by the radio drug used and its price often varies from 300 to 500 Euros for each dose used for the patient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The availability of commercial sources of 18 F-FDG and its purchase on a unit dose basis allows the operation of a PET imaging center without the prohibitive overhead costs of operating and maintaining a cyclotron [4][5][6]. As a result of the widespread availability of 18 F-FDG, many of the PET and PET/computed tomography (CT) imaging centers in existence today are single-camera facilities.…”
Section: Introductionmentioning
confidence: 99%